The real wealth of nations : creating a caring economics - Eisler, Riane Tennenhaus (BK currents book., 2007)
Social scientist Eisler shows that the great problems of our time--such as poverty, inequality, war, terrorism, and environmental degradation--are due largely to flawed economic systems that set the wrong priorities and misallocate resources. Conventional economic models fail to value and support the most essential human work--caring and caregiving--so basic human needs are increasingly neglected, despair and ecological destruction escalate, and the resulting social tensions fuel many of the conflicts we face today. Eisler offers a bold reformulation: a caring economics that transcends traditional categories like capitalist and socialist and offers enormous economic and social benefits. She describes how to put this model into practice through new government and business policies and practices, innovative economic indicators that incorporate caregiving activities, and new social structures. And she lays out practical steps we can take to move towards a society based on this more humane economic model.--From publisher description.